Влияние структуры и фазового состава на коррозионную стойкость сварных соединений дуплексных нержавеющих сталей - Белоев, М.; Хартунг, Ф.; Лолов, Н.; Александров, Б. (Автоматическая сварка, 2003)
Рассмотрены состав, структура, металлургические свойства современных дуплексных нержавеющих сталей. Показано влияние легирующих элементов, фазового состава сталей, а также термического цикла сварки на механические свойства и коррозионную стойкость различных участков сварных соединений дуплексных сталей. Properties and applications of a comparatively new group of high-alloyed stainless steels that has been introduced in practice since 1970s are reviewed in this report. These are so called duplex stainless steels, the structure of which consists of approximately equal quantities of austenite and ferrite. These steels have many advantages compared to the traditional austenitic stainless steels. Their advantages result in increasingly wider use of duplex stainless steels in many industry branches as petrochemical industry, especially in off-shore installations, in chemical industry in installations for pulp and paper, in installation for fertilizers etc., in energetic industry for fuel gas desulphurisation, in shipbuilding for chemical tankers, in mining industry in installations for extracting of different ores, in pharmaceutics and so on. The present report represents a first stage of research project for implementation of duplex stainless steels in the Bulgarian industry, performed jointly by the Technical University of Sofia and KZU Holding Ltd. Under the current stage of the project the optimal implementation of pulsed gas metal arc process for welding of duplex stainless steels is being investigated.